Synthesis and pharmacological evaluation of 99mTc‐labeled imidazolyl‐containing diphosphonic acid as a novel bone imaging agent. (16th September 2013) - Qiu, Ling; Cheng, Wen; Lin, Jianguo; Zhang, Shu; Luo, Shineng
<x xml:space="preserve">Abstract</x> In order to develop a superior bone imaging agent, a new radiotracer 99mTc‐1‐hydroxy‐5‐(2‐butyl‐1H‐imidazol‐1‐yl)pentane‐1, 1‐diyldiphosphonic acid (BIPeDP) was designed and prepared with good radiochemical yield and stability. The biodistribution in mice shows that 99mTc‐BIPeDP has high specificity in the skeleton with the maximum uptake of 17.30 ± 0.14 injected dose per gram at 60 min. Kinetics of blood clearance shows that the distribution half‐life (T1/2α) and elimination half‐life (T1/2β) of 99mTc‐BIPeDP are 3.7 and 49.7 min, respectively. An excellent image can be obtained at 1‐h post‐injection with the single photon emission computed tomography bone scanning, which is clearer and quicker than 99mTc‐zoledronic acid, 99mTc‐1‐hydroxy‐5‐(1H‐imidazol‐1‐yl)pentane‐1, 1‐diyldiphosphonic acid, and 99mTc‐methylenediphosphonic acid All results indicate that 99mTc‐BIPeDP holds great potential as a novel promising bone imaging agent. Copyright © 2013 John Wiley & Sons, Ltd.